Асимптотическое разложение решений квазилинейных параболических задач в перфорированных областях - Скрыпник, И.В. (Український математичний журнал, 1993)
The asymptotic expansion of solutions to quasilinear parabolic problems with the Dirichlet boundary condilions is constructed in the regions with a fine-grain boundary. It is shown that the sequence of the remainders of the expansion strongly converges to zero in the space W1,1/22.